Initial experience with a physiological, rate responsive pacemaker. Issue 6366 (26th February 1983) - Donaldson, R M; Fox, K; Rickards, A F
Abstract : A new pacemaker that can adapt the heart rate in response to the patient's metabolic requirements has been developed. This pacemaker uses the QT interval as the indicator of physiological demand. Experience in five patients showed the rate response to exercise to be smooth and progressive and to return gradually to the basic paced rate after activity stopped. Physiological rate responsive pacing resulted in a 45% increase in cardiac output when compared with fixed rate pacing. Similarly, a 57% increase in maximal exercise capacity was noted when rate responsive pacing was compared with conventional pacing at 70 beats/min. This study showed that physiological rate responsive pacing using the QT interval provides a simple means of increasing the heart rate in accordance with the body's requirements.